Development of a decision support system for the selection of wastewater treatment technologies - Ullah, Abaid; Hussain, Salman; Wasim, Ahmad; Jahanzaib, Mirza (The Science of the total environment, 2020)
Multiple factors including technical, social, economic, regulatory, governmental, and environmental add complexity in the process of selecting a suitable wastewater treatment technology. To overcome this issue, this paper aims to propose a decision support system (DSS) for the selection of wastewater treatment technologies. The proposed system has been developed using a detailed review of the state-of-the-art in wastewater treatment, implemented using Microsoft Visual Studio 2010 and validated through real-time case studies. The system is categorized into four treatment levels based on wastewater complexity and the required degree of treatment. These include preliminary, primary, secondary, and tertiary treatment. Based on the identified treatment levels, the proposed system suggests using any physical, biological, chemical, or hybrid treatment process. The developed DSS will aid the selection of suitable wastewater treatment technology from a set of alternatives while keeping user constraints, conflicting requirements, and prevailing conditions under consideration. Moreover, the system is capable to customize the treatment assembly at the planning stage with minimized costs, eliminate mistakes at the planning and design stage, facilitate decision making by narrowing down the alternative solution as per user requirements and prevailing conditions, incorporate customer demand, and promote sustainable development. [Display omitted] •A DSS has been developed for the selection of wastewater treatment technologies.•A facile approach has been used to assist both expert/non-expert users.•The system has been applied using Windows Forms in Microsoft Visual Studio 2010.•Recommended for researchers, designers, wastewater engineers and policy makers